Fabrication of urchin-like NiCo2(CO3)1.5(OH)3@NiCo2S4 on Ni foam by an ion-exchange route and application to asymmetrical supercapacitors1. Issue 25 (7th July 2015) - Yang, Bin; Yu, Lei; Yan, Huijun; Sun, Yanbo; Liu, Qi; Liu, Jingyuan; Song, Dalei; Hu, Songxia; Yuan, Yi; Liu, Lianhe; Wang, Jun
<x xml:space="preserve">Abstract</x> We synthesized the urchin-like NiCo2(CO3)1.5(OH)3@NiCo2S4 which has a high electrochemistry response capability and cycle stability by the ion exchange route.